2015
DOI: 10.1136/thoraxjnl-2015-207770.322
|View full text |Cite
|
Sign up to set email alerts
|

P185 Evaluation of the LENT Prognostic Score in a Large Tertiary Pleural Service

Abstract: Introduction and objectivesReliable predictors of survival in malignant pleural effusions (MPE) have far reaching applications in clinical practice, not least tailoring individual treatment strategies. The ‘LENT’ score (pleural fluid Lactate dehydrogenase; Eastern Cooperative Oncology Group performance score; Neutrophil-to-lymphocyte ratio; Tumour type) was developed and validated as a clinical prognostic scoring system from three international prospective patient databases.1 The aim of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Prior validation of the LENT score in Caucasian cohorts do not translate to our patients. The LENT score C‐statistic in our cohort was the lowest when compared to three other studies validating LENT that reported C‐statistics (0.56 vs 0.75, 0.62 and 0.69) (Table S3 in Supplementary Information) 7,8,12 . The reason for this discrepancy may be attributed to the disparate frequency of EGFR mutations seen in Asian cohorts 10 .…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Prior validation of the LENT score in Caucasian cohorts do not translate to our patients. The LENT score C‐statistic in our cohort was the lowest when compared to three other studies validating LENT that reported C‐statistics (0.56 vs 0.75, 0.62 and 0.69) (Table S3 in Supplementary Information) 7,8,12 . The reason for this discrepancy may be attributed to the disparate frequency of EGFR mutations seen in Asian cohorts 10 .…”
Section: Discussioncontrasting
confidence: 61%
“…26 Other reasons for the discrepant LENT C-statistic may be attributable to younger patients in our study (65 IQR (56-71) vs 74 IQR (67-80) years), a larger proportion of patients with better functional status (ECOG 0-1) (81% vs 54%) and possibly fewer medical comorbidities as all our patients underwent pleuroscopy. 7 In terms of median survival, our study is the third Asian study validating the LENT score that reports discordant results from other studies [10][11][12]14,15 (Table S4 in Supplementary Information). Clinical use of the existing LENT model is precluded in an Asian population as it significantly underestimates survival.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations